Analisis Perbandingan Kinerja Aplikasi Android Java dan Kotlin dalam Mengonsumsi API - Pratama, Rendy; Farisi, Ahmad; Alamsyah, Derry (MDP Student Conference, 2025)
This study investigates the performance of android applications developed using Java and Kotlin in consuming API. Driven by the need for responsive and efficient android applications and the potential impact of runtime performance differences between Java and Kotlin programs, this research employs an experimental method with a quantitative approach. Data is collected through Instrumented Tests and Android Studio tools on two smartphones with different specifications. Parameters measured include data download speed, memory allocation, execution time, serialization/deserialization time, application size, and lines of code. Results indicate Java's superiority in download speed and data serialization, while Kotlin demonstrates conciseness in code size. Performance varies depending on device specifications. The choice of programming language depends on the application's needs and priorities. Java is optimal for applications prioritizing download speed and data serialization, while Kotlin suits those focused on code efficiency. This study provides recommendations for PANDA application developers and future research.